A protocol for unguided internet self-help cognitive behaviour therapy for perfectionism in adolescents at-risk of eating disorders - O'Brien, Amy; Anderson, Rebecca; Mazzucchelli, Trevor; Egan, Sarah (Elsevier, 2022)
Perfectionism has a strong association with eating disorders, anxiety and depression. Unguided internet cognitive behaviour therapy for perfectionism has demonstrated efficacy in female adolescents without elevated eating disorder symptoms. No research to date has examined unguided internet cognitive behaviour therapy for perfectionism for adolescents with elevated eating disorder symptoms as an indicated prevention for eating disorders and co-occurring symptoms of anxiety and depression. The protocol outlines the plan for a randomised controlled trial of a co-designed, unguided internet cognitive behaviour therapy for perfectionism with female adolescents with elevated symptoms of eating disorders. The intervention will be a 4-week programme compared to a waitlist control. Outcomes on eating disorder symptoms, anxiety and depression will be measured pre and post intervention and follow-up.